Cluster analysis of long-term phytoplankton data from the Northern Adriatic reveals environmental influences and disruptions in seasonal patterns - Vlašiček, Ivan; Marić Pfannkuchen, Daniela; Smodlaka Tanković, Mirta; Baričević, Ana; Kužat, Nataša; Knjaz, Mia; Grižančić, Lana; Podolšak, Ivan; Kogovšek, Tjaša; Pfannkuchen, Martin (Frontiers in Ecology and Evolution, 2025)
The Northern Adriatic is a dynamic and the most productive part of the Adriatic Sea. The phytoplankton of the Northern Adriatic is, as many studies in this area showed, under heavy influence of freshwater inputs and anthropogenic pressures. Cluster analysis of a more than 20 year phytoplankton data set across steep spatio-temporal, ecological gradients on a longitudinal transect across the northern Adriatic, allowed us to identify significant and reoccurring phytoplankton species assemblages. Those phytoplankton clusters show stable seasonality and relation to environmental conditions and are presumed to be cornerstones of important ecosystem services provided by phytoplankton. Our results demonstrate that the stable seasonality of important phytoplankton clusters is disrupted, leading to a destabilisation of seasonal patterns in the biodiversity of primary producers. During the last 20 years, clusters characterised by dominating species were replaced by clusters characterised by the coexistence of several species. Overall the frequency of dense blooms of single species appears to decline. Multivariate analysis showed that possible reasons might lie in oligotrophication and increased salinity dynamics. Our results suggest the importance and applicability of cluster analysis in taxon based biodiversity long term data sets to elucidate functional biodiversity changes.